Pulmonary function after lobectomy in children: a systematic review and meta-analysis - Jie Liu; Chang Xu; Li Zeng; Chenyu Liu; Miao Yuan; Kaisheng Cheng; Dengke Luo (BMJ Publishing Group, 2023)
Background The influence of lobectomy on pulmonary function in children was still controversial. A systematic review and meta-analysis were essential to explore whether pulmonary function was impaired after lobectomy in children.Methods PubMed, Embase and Web of Science were searched from 1 January 1946 to 1 July 2022. Forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), FEV1/FVC and total lung capacity were extracted from the studies as the primary analysis indicators. Subgroup analyses were performed between the congenital lung malformation (CLM) group and other diseases group, early surgery and late surgery group (1 year old as the dividing line).Results A total of 5302 articles were identified through the search strategy; finally, 10 studies met the inclusion criteria. Through the meta-analysis, we found a mild obstructive ventilatory disorder in children who underwent lobectomy. However, a normal pulmonary function could be found in young children with CLM who underwent lobectomy, and the time of operation had no significant influence on their pulmonary function.Conclusions The overall result of pulmonary function after lobectomy in children was good. Surgeons may not need to be excessively concerned about the possibility of lung surgery affecting pulmonary function in children, particularly in patients with CLM.PROSPERO registration number CRD42022342243.